2010
DOI: 10.3340/jkns.2010.47.2.151
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Cervical Spinal Cord Stimulation Used to Treat Intractable Pain Arising from Transverse Myelitis Caused by Schistosomiasis

Abstract: J Korean Neurosurg Soc 47 : [151][152][153][154] 2010 The efficacy of spinal cord stimulation (SCS) for treatment of various chronic painful conditions is well established. Very few reports have documented the use of SCS for treatment of chronic pain after spinal cord injury. We present a case showing a good outcome after such treatment, and suggest that high cervical stimulation may be efficacious. A 53-year-old male underwent SCS on the C1-3 level for treatment of intractable neuropathic pain below the T3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Twenty‐two reports were identified that included at least 1 patient with neuropathic pain from SCI treated with SCS. Five were published case reports, 1 was a prospective nonrandomized, noncontrolled study, and the remaining 16 were case series or reports published as conference abstracts . All reports other than that of Kishima et al were retrospective in nature.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐two reports were identified that included at least 1 patient with neuropathic pain from SCI treated with SCS. Five were published case reports, 1 was a prospective nonrandomized, noncontrolled study, and the remaining 16 were case series or reports published as conference abstracts . All reports other than that of Kishima et al were retrospective in nature.…”
Section: Resultsmentioning
confidence: 99%
“…However, the prognosis is poor, and usually intractable chronic courses are followed. A few case reports have described the control of neuropathic pain in patients with TM via SCS [6–8] . Here, we present a successful case of pain control after inserting an ITP into a patient with recurring Sjögren's syndrome-related TM.…”
Section: Introductionmentioning
confidence: 91%
“…A few case reports have described the control of neuropathic pain in patients with TM via SCS. [6][7][8] Here, we present a successful case of pain control after inserting an ITP into a patient with recurring Sjögren's syndrome-related TM. This study was approved by the Ethical Committee of the Seoul St. Mary's Hospital.…”
Section: Introductionmentioning
confidence: 99%